General microbiology teaching adaptation in the covid-19 period: Pre-service teacher perspectives and experiences - Rida Oktorida Khastini; Nani Maryani; Suroso Mukti Leksono (JURNAL BIOEDUKATIKA, 2021)
As a result of the COVID-19 global pandemic, teaching activity for pre-service teachers enrolled in the second year of a teacher education program from mid-March of 2020/2021 at the Universitas Sultan Ageng Tirtayasa were changed in a remote learning setting. This study's objective was to investigate pre-service students' perceptions and personal experience toward the transition of General microbiology lecture to online learning during the global COVID-19 pandemic. The results described the efforts and adaptation to an online teaching model of the General Microbiology course using both online synchronous and asynchronous learning. The perspectives of the Pre-Service Teacher about this strategy were analyzed and showed positive responses. Despite some challenges, they could adapt to the new learning methods. In addition, the study also provided an analysis of faculty readiness and experiences through a process that can use as a foundation to tackle the pandemic situation in the future.